Waspada Gangguan Pernapasan: Peran Skrining Spirometri dalam Pencegahan Penyakit Paru di Kelurahan Grogol - Kosasih, Robert; Santoso, Alexander Halim; Gunaidi, Farell Christian; Alvianto, Fidelia; Pratama, Aditya (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Lung health plays a vital role in maintaining individual productivity and metabolic functions, especially in adults. Early detection of pulmonary function decline is essential, as respiratory disorders such as chronic obstructive pulmonary disease (COPD) and asthma often develop insidiously. This community service program aimed to conduct early screening of lung function using spirometry in Grogol Subdistrict, West Jakarta, targeting the productive-age population. The activity followed a Plan-Do-Check-Act (PDCA) cycle, beginning with public education and proceeding to spirometry tests, result evaluations, and follow-up medical advice. A total of 71 participants were involved, with a mean age of 43.6 years. The average spirometric values were: Vital Capacity (VC) 2.32 L, Forced Vital Capacity (FVC) 2.09 L, Forced Expiratory Volume in 1 second (FEV1) 1.95 L, and FEV1/FVC ratio of 92.14%. Most participants (98.6%) were categorized as